Perceptions and attitudes of medical students towards student evaluation of teaching: A cross-sectional study - Abdulkarim S. Almakadma; Nader Ashraf; Omar J. Baqal; Sudha Kamada (Medical Education Online)
Background Faculty evaluation surveys in the frame of student evaluation of teaching (SETs) are a widely utilized tool to assess faculty teaching. Although SETs are used regularly to evaluate teaching effectiveness, their sole use for making administrative decisions and as an indicator of teaching quality has been controversial.Methods A survey containing 22 items assessing demographics, perceptions, and factors for evaluating faculty was distributed to medical students at our institute. Statistical analyses were conducted using Microsoft Excel and R Software utilizing regression analysis and ANOVA tests.Results The survey received 374 responses, consisting of 191 (51.1%) male students and 183 (48.9%) female students. In all, 178 (47.5%) students considered the optimal time for providing faculty evaluation to be after the release of the exam results, compared to 127 (33.9%) students, who chose the after the exam but before the release of exam results option. When asked what happens whenever the tutor is aware of the SETs data, 273 (72.9%) and 254 (67.9%) students believed that it would influence the difficulty of the exam and the grading/curving of the exam results, respectively. Better teaching skills (93%, 348), being responsive and open to student feedback and suggestions (84.7%, 317), being committed to class time and schedule (80.1%, 300), and an easier exam (68.6%, 257) were considered important factors to acquire a positive evaluation by a considerable proportion of students. Fewer lectures (p < 0.05), decreased number of slides per lecture (p < 0.01), easier exam (p < 0.05), and giving clues to students about the exam (p < 0.05) were found to be very important to obtain a positive tutor evaluation by students.Conclusions Institutions ought to continue exploring areas for improvement in the faculty evaluation process while raising awareness among students about the importance and administrative implications of their feedback.